Phylogenetic and population studies of geophytic Euphorbia species (subgenus Euphorbia) from some deciduous forests and hill top plateaus in India. Issue 2 (3rd July 2018) - Jagtap, Ashwin; Maurya, Satish; Jadhav, Pooja; Dighe, Bhushan; Kashikar, Akanksha; Punekar, Sachin; Sardesai, Milind; Karmalkar, Nitin; Bhargava, Sujata
ABSTRACT: Geophytic Euphorbia species are distributed across four sections in subgenus Euphorbia of genus Euphorbia . At least nine Indian geophytic Euphorbia species have been identified, but delimitation of these species is controversial. Phylogenetic studies using nuclear ribosomal internal transcribed spacers (nrITS) and matK sequences showed that the Indian geophytic Euphorbia species lie within the section Euphorbia clade that includes African and Indian non-geophytic species. Ribotype/ haplotype analysis of nrITS and matK sequences revealed that the populations of Euphorbia fusiformis and Euphorbia nana could not be distinguished on this basis. Population studies based on nrITS sequences showed significant gene differentiation between the populations from different localities. The Indian geophytic Euphorbia species showed morphological variation in their leaf and cyathial characters, which correlated with the variation in soil composition of their habitats. Our studies suggest that local adaptation and phenotypic plasticity are responsible for taxonomic ambiguities in the classification of Indian geophytic Euphorbia species.